Menumbuhkan Kesadaran Sejarah Generasi Muda Melalui Kearifan Lokal Budaya Melayu Riau - Asril Asril (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2022)
It is important to inculcate historical awareness for the younger generation. This study aims to explore the local wisdom of the Malay community in order to publish historical stories to the younger generation. This study uses a qualitative method with interview techniques and literature study in collecting data. The results of the study found that efforts in the process of socializing local history in the community were through education and instilling curiosity in local historical stories. In addition, the availability of supporting facilities and infrastructure plays an important role in facilitating the community to learn, explore and know about local history in their area. Publication activities and seminars are one way to make it easier for people to know local history, because with these publications and seminars, people will be able to interact directly with resource persons to gain additional knowledge and exchange information. The use of Malay traditions such as Syair and Gurindam by focusing on historical stories is an interesting thing that needs to be developed in the era of globalization to maintain regional culture.